2020
DOI: 10.1007/s00441-020-03206-9
|View full text |Cite
|
Sign up to set email alerts
|

The pig as a model for immunology research

Abstract: The pig is an omnivorous, monogastric species with many advantages to serve as an animal model for human diseases. There are very high similarities to humans in anatomy and functions of the immune system, e g., the presence of tonsils, which are absent in rodents. The porcine immune system resembles man for more than 80% of analyzed parameters in contrast to the mouse with only about 10%. The pig can easily be bred, and there are less emotional problems to use them as experimental animals than dogs or monkeys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(134 citation statements)
references
References 165 publications
3
118
0
Order By: Relevance
“…Because of the anatomical, physiological, and immunological similarities of human and porcine intestine, pigs have been considered an attractive model to study the mechanisms involved in intestinal diseases as well as the interaction of microbes with the immune system (64). In this work, we demonstrated that PIE cells could give us the possibility of conducting in vitro studies to evaluate the epithelial barrier function, the innate immune response, and the influence of immunomodulatory beneficial microbes on those parameters, in the context of DSS challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the anatomical, physiological, and immunological similarities of human and porcine intestine, pigs have been considered an attractive model to study the mechanisms involved in intestinal diseases as well as the interaction of microbes with the immune system (64). In this work, we demonstrated that PIE cells could give us the possibility of conducting in vitro studies to evaluate the epithelial barrier function, the innate immune response, and the influence of immunomodulatory beneficial microbes on those parameters, in the context of DSS challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Among LAM, pigs are the most popular large animals used in the kidney research ( Figure 1 ). Pigs share more than 80% of immune parameters with humans as compared to mice that share less than 10% [ 22 , 23 , 55 ]. Similar to humans, and in contrast to mice, pigs have a high percentage of neutrophils in the peripheral blood (50–70%), express CXCL8/IL-8, do not express iNOS in macrophages, IFN-γ and LPS stimulate IDO in macrophages, and pigs are sensitive to endotoxin shock [ 23 , 56 ].…”
Section: The Differences In Innate Immunity Among Rodents Large Animmentioning
confidence: 99%
“…Minipig brain size and neuroanatomy also make them suitable for neurosurgical procedures and non-invasive imaging methods similar to those used in human diagnostics [ 26 ]. Minipig physiology [ 25 ], and immune responses (around 80% similarity) [ 27 – 29 ], are more similar to those in humans when compared to lower vertebrates.…”
Section: Sheep Modelsmentioning
confidence: 99%